Analisis Pemakaian Energi Pada Sensor Node Dengan Protokol Komunikasi Zigbee Menggunakan Solar Cell - Nur Cahyo Utomo; Rakhmadhany Primananda; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Communication protocol on OSI Layer standardization, divided into several layers among them is data link layer. This layer divided into sub layers, one of which is MAC (Medium Access Control) used to transmit signals owned by nodes connected to the network without any conflict. Zigbee is one of the standardized communication protocols on the MAC sub layer that are known to be reliable and low power. With zigbee, the researcher has the idea of ​​analyzing the power consumption level when this protocols are communicates. The communication system between the nodes was tested using xbee s-1 with arduino uno as microcontroller, and because xbee s-1 low power researchers gave solar cells as resources. Solar cells are used because they have self charging capabilities. System testing includes, changes in environmental conditions when nodes communicate. The last step in this research is to analyze the result data from the test to conclude the result of the research. The result of this research is zigbee communication using solar cell resources can be used in areas where the air temperature is stable and there are heat sources. The power of calor can provide arduino microcontroller power and xbee s-1 module to be used in communicating. Changes in working environment in the form of distance, delivery of packets, temperature, and time intervals applied by researchers can affect the level of power consumption. Researchers recommend environmental conditions that are used so that the system can be run optimally. The use of the zigbee protocol would be optimal if used at a distance of 60-70 m, data transmission by 60 - 80 bytes, temperatures at <30 and> 20 ° celcius, and time intervals 25-35 seconds.